2021
DOI: 10.3389/fonc.2021.761379
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis and Therapeutic Aspects of Cisplatin Resistance in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a kind of malignant tumors with low survival rate and prone to have early metastasis and recurrence. Cisplatin is an alkylating agent which induces DNA damage through the formation of cisplatin-DNA adducts, leading to cell cycle arrest and apoptosis. In the management of advanced OSCC, cisplatin-based chemotherapy or chemoradiotherapy has been considered as the first-line treatment. Unfortunately, only a portion of OSCC patients can benefit from cisplatin treatment, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 180 publications
(146 reference statements)
0
39
0
Order By: Relevance
“…Moreover, it has shown a tumor growth delay when exposed to current standard chemotherapeutic regimens (20). However, chemotherapeutic agent selectivity kills proliferating cells over quiescent cells (21), triggering cancer stem cell enrichment (quiescent cells) and favoring resistance to chemotherapy (22). An example of that is the quiescent area increase in the treated spheroids in our results.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, it has shown a tumor growth delay when exposed to current standard chemotherapeutic regimens (20). However, chemotherapeutic agent selectivity kills proliferating cells over quiescent cells (21), triggering cancer stem cell enrichment (quiescent cells) and favoring resistance to chemotherapy (22). An example of that is the quiescent area increase in the treated spheroids in our results.…”
Section: Discussionmentioning
confidence: 53%
“…Since our findings in Fig. 5 indicated that depletion of KRT17 by miR485-5p elevated OSCC cellular sensitivity toward the frequently used first-line chemotherapeutics, cisplatin and carboplatin [ 54 , 55 ]. To further confirm those observations, we inhibited directly KRT17 by its siRNA in C9IV3 and HSC3 cells and tested their sensitivity toward cisplatin or carboplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin-based chemotherapy is the first-line chemotherapy agent for OSCC [12]. Cisplatin covalently binds to the N7 position of the purine base of DNA, forming adducts such as intra-strand cross links, which trigger cytotoxicity [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blocking DNA repair pathway is an important approach for tumor treatment. For instance, cisplatin, the first-line chemotherapeutic drug for OSCC, induces DNA damage through the formation of cisplatin-DNA adducts, leading to cell cycle arrest and apoptosis [ 12 ]. Nucleotide excision repair is a key pathway to resist damage caused by cisplatin [ 13 ].…”
Section: Introductionmentioning
confidence: 99%